Discounting trillions of dollars in pension obligations: A better alternative to using the expected return or risk-free rate - Tiemen Woutersen (Centre for Microdata Methods and Practice (cemmap), 2022)
This paper proposes a new discount rate that pension funds can use to discount their future obligations. If the payouts of a pension fund depend on the return of the fund's assets, then neither the risk-free rate nor the expected return is an equitable way to discount future liabilities. Using the newly proposed rate, the expected utilities of a particular stream of payments are the same in each period. This proposed rate is higher than the discount rate that is used by some pension funds but lower than the rate that the U.S. States are required to use.
Keywords: G20; G28; H60; H55; H50; 330; Discount rate; Pension fund obligations; valuation future obligations